Thermal stability of woodfibers produced from recycled medium density fiberboards : Toplinska stabilnost drvenih vlakana proizvedenih od recikliranih srednje gustih ploča vlaknatica - Ahmadi, Mohammad (Array, 2019)
In this study, thermal stability of fibers obtained from recycled MDF was investigated and compared with virgin fibers by using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Two different methods, including electrical heating and hydrothermal treatment, were used for recycling the MDF wastes. Electrical heating method was performed at two different times (2 and 4 min) and hydrothermal method was done at three different temperatures (105, 125 and 150 °C). Chemical structure of wood fibers was also studied. TGA and DSC analysis showed higher weight loss of recycled fibers as compared to virgin fibers in a similar degradation region, which means that thermal stability of recycled fibers is lower than virgin fibers. In fact, thermal behavior of recycled fibers was medium between wood and UF resin. DSC analysis showed two exotherms at around 340 and 475 °C. The transition at around 340 °C in fibers thermogram was considered to be due to polysaccharides thermal deterioration and the exotherm at 475 °C was related to lignin carbohydrate complex deterioration. The results of chemical structure analysis showed that lignin and hemicellulose content of recycled fibers was significantly lower than that of virgin fibers, which resulted in decreased thermal stability.